Characteristics of anginal patients with high resting myocardial blood flow measured with N-13 ammonia PET/CT. Issue 6 (June 2015) - Cho, Sang-Geon; Kim, Ju Han; Cho, Jae Young; Kim, Hyeon Sik; Kwon, Seong Young; Bom, Hee-Seung
<x xml:space="preserve">Abstract</x> Objectives We hypothesized that anginal patients with low coronary flow reserve (CFR) could have variable clinical features according to resting myocardial blood flow (MBF). Therefore, we analyzed the clinical and imaging characteristics according to resting MBF in anginal patients. Methods We enrolled 70 patients who underwent N-13 ammonia PET–computed tomography (CT) for evaluation of angina. Resting and stress MBF values were obtained and resting MBF was corrected with rate–pressure product to exclude the effect of heart rate and blood pressure on resting MBF. Clinical and imaging characteristics were compared on the basis of MBF and CFR. Results Among patients with CFR less than 2.0, those with high resting MBF (≥1.0 ml/min/g) had significantly fewer number of smokers, were younger, had lower Agatston calcium scores, and had less coronary stenosis compared with those with low resting MBF (<1.0 ml/min/g). In contrast, there was no significant difference in clinical or imaging findings according to resting MBF when compared among all patients or within those with CFR greater than or equal to 2.0. The subgroup analysis of patients with CFR less than 2.0 revealed lower Agatston calcium score and less coronary stenosis in patients with high resting MBF regardless of stress MBF. Conclusion High resting MBF is associated with a lower rate of smoking, younger age, less coronary calcium burden, and less coronary stenosis compared with low resting MBF in anginal patients with low CFR. Moreover, in these patients, favorable angiographic features were mainly associated with high resting MBF, irrespective of stress MBF. Therefore, resting MBF should be reviewed to validate the clinical significance of low CFR measured by N-13 ammonia PET/CT especially in anginal patients showing low CFR.